Study on Mechanical Properties of Pineapple Leaf-Glass Fiber Hybrid Composites for Car Body Applications - Sutrisno; Sudarno; Wahidin Nuriana; Koharudin Koharudin (Journal of Railway Transportation and Technology, 2023)
The purpose of this study was to determine the mechanical properties of glass fiber composites and fiber, orientation and variations pineapple with a different composition of the main tarik.Bahan tests used are glass fiber, pineapple fiber, lye (NaOH), epoxy resin and hardener. Specimens composites made by the method of hand lay up with variations in the composition of the glass fiber 6%: pineapple fiber 4%, the glass fiber 9%: pineapple fiber 6%, glass fibers 12%: pineapple fiber 8%, glass fibers 15%: pineapple fiber 10% and with random fiber orientation and horizontal. Making the specimens was performed by reference to standard ASTM D 638.Hasil this test shows that the highest tensile strength in horizontal fiber orientation with the volume fraction of 25% sebesar143.98 MPa, while the lowest occurred in a random fiber orientation of 10% amounting to 13.45 MPa. Fault Composite glass fiber and epoxy pineapple fiber bermatrik average can be classified as a single fracture type.